Peran Fasilitasi Program Inkubasi Wirausaha pada Dinas Koperasi dan UMKM Kota Cilegon dalam Peningkatan Daya Saing UMKM di Kota Cilegon - Alivia Fitri Salsabila; Ria Yuni Lestari; Wika Hardika Legiani (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
This study aims to analyze the role of facilitation of the entrepreneurship incubation program organized by the Cooperative and UMKM Office of Cilegon City in increasing the competitiveness of UMKM. UMKM (Micro, Small, and Medium Enterprises) have an important role in regional economic growth, including Cilegon City. The Cilegon City Government through the Cooperative and UMKM Office organizes an entrepreneurship incubation program as a form of facilitation to help UMKM develop. The entrepreneurship incubation program is an effort to provide support and assistance to UMKM so that they can develop and be competitive. The research method used is descriptive with a qualitative approach and the data collection techniques used consist of interviews, observations, and documents. The research respondents consisted of participants in the entrepreneurship incubation program and the Cooperative and UMKM Office of Cilegon City. The results of the study obtained are The results of the study indicate that the entrepreneurship incubation program has an important role in increasing the competitiveness of UMKM in Cilegon City. The Cooperative and UMKM Office acts as a facilitator in the planning, implementation, and evaluation of the entrepreneurship incubation program. This program is designed to increase the capacity and independence of UMKM through training, mentoring, and access to capital. However, there are several obstacles such as the lack of active participation from UMKM actors and limited resources. The strategies implemented include improving the quality of training, cooperation with external parties, and periodic evaluations. The right recommendation according to the results of this study is the need for a comprehensive investigation of concerns about the condition of UMKM in several aspects of the problems faced. Periodic evaluation of the entrepreneurial incubation program is needed so that it becomes a complete incubation service program and can run optimally.